2020
DOI: 10.1042/ebc20200016
|View full text |Cite
|
Sign up to set email alerts
|

Alerting the immune system to DNA damage: micronuclei as mediators

Abstract: Healthy cells experience thousands of DNA lesions per day during normal cellular metabolism, and ionizing radiation and chemotherapeutic drugs rely on DNA damage to kill cancer cells. In response to such lesions, the DNA damage response (DDR) activates cell-cycle checkpoints, initiates DNA repair mechanisms, or promotes the clearance of irreparable cells. Work over the past decade has revealed broader influences of the DDR, involving inflammatory gene expression following unresolved DNA damage, and immune surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 118 publications
(155 reference statements)
0
20
0
Order By: Relevance
“…DNA double-strand breaks are the most lethal lesions induced by ionizing radiation and can trigger a series of cellular DNA damage responses (DDRs). Recently, a review described the current evidence linking the DNA damage responses to activation of the immune response through micronuclei formation 35 . It has been demonstrated that proton therapy induced more DNA double-strand breaks and micronuclei than photon irradiation at equivalent doses (2–12 Gy) 36 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA double-strand breaks are the most lethal lesions induced by ionizing radiation and can trigger a series of cellular DNA damage responses (DDRs). Recently, a review described the current evidence linking the DNA damage responses to activation of the immune response through micronuclei formation 35 . It has been demonstrated that proton therapy induced more DNA double-strand breaks and micronuclei than photon irradiation at equivalent doses (2–12 Gy) 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous GFP-BLM expression reduced the frequency of micronuclei in U2OS 8 E6 cells (Figure 3D). Micronuclei contain either whole (centric) or partial (acentric) chromosomes depending on how they form (54)(55)(56)(57). Unrepaired DSBs lead to smaller acentric micronuclei (58), whereas segregation errors result in larger centric micronuclei (59,60).…”
Section: E6 Increases Micronuclei Frequency In Part Through Blm Reduc...mentioning
confidence: 99%
“…In general, unresolved DNA damage can act as a mediator linking the DDR and immune recognition, and this can involve the formation of micronuclei as an initiating event in a cascade promoting genomic instability and innate immune responses ( 78 , 79 ). Moreover, genome instability and imperfect cell cycle checkpoints in tumor cells enhance formation of micronuclei, making them more susceptible to targeting of the innate immune response ( 5 , 22 , 79 ).…”
Section: Ddr In Innate Immunitymentioning
confidence: 99%